2023
DOI: 10.1111/jbi.14708
|View full text |Cite
|
Sign up to set email alerts
|

Forests on the move: Tracking climate‐related treeline changes in mountains of the northeastern United States

Jordon Tourville,
David Publicover,
Martin Dovciak

Abstract: AimAlpine treeline ecotones are influenced by environmental drivers and are anticipated to shift their locations in response to changing climate. Our goal was to determine the extent of recent climate‐induced treeline advance in the northeastern United States, and we hypothesized that treelines have advanced upslope in complex ways depending on treeline structure and environmental conditions.LocationWhite Mountain National Forest (New Hampshire) and Baxter State Park (Maine), USA.TaxonHigh‐elevation tree speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 86 publications
1
1
0
Order By: Relevance
“…This variable is more readily estimated and included in the standardized set of bioclimatic variables under the BIO10 code (Hijmans et al 2005). Our ndings align with the study of treeline changes in the northeastern United States, where AGDD was found to signi cantly account for variations in the extent of treeline advancement (Tourville et al 2023). We do not, however, assert the universal applicability of these results.…”
Section: Factors Determining the Treeline Positionsupporting
confidence: 77%
See 1 more Smart Citation
“…This variable is more readily estimated and included in the standardized set of bioclimatic variables under the BIO10 code (Hijmans et al 2005). Our ndings align with the study of treeline changes in the northeastern United States, where AGDD was found to signi cantly account for variations in the extent of treeline advancement (Tourville et al 2023). We do not, however, assert the universal applicability of these results.…”
Section: Factors Determining the Treeline Positionsupporting
confidence: 77%
“…Diffuse treelines are more often limited by climatic factors, unlike abrupt and krummholz treelines, which are more likely to be shaped by anthropogenic and natural disturbances (Harsch et al 2009;Hansson et al 2021). It is indirectly con rmed by gradual diffuse treelines being more responsive to climate warming (Tourville et al 2023). We manually delineated treeline ecotones on high-resolution Bing images.…”
Section: Treeline Delineationmentioning
confidence: 99%